Transmission Problem in Thermoelasticity. (9th March 2011) - Alves, Margareth S.; Muñoz Rivera, Jaime E.; Sepúlveda, Mauricio; Vera Villagrán, Octavio
Abstract : We show that the energy to the thermoelastic transmission problem decays exponentially as time goes to infinity. We also prove the existence, uniqueness, and regularity of the solution to the system.